A useful empirical tool box for distributional analysis - Charles M. Beach (Queen's University, Department of Economics, 2021)
This paper offers a tool box of disaggregative measures of distributional change, including population shares, income shares, quantile mean incomes and relative mean incomes of different income groups. It highlights median-based measures along with quintiles and deciles. It also offers formulas for the measures' standard errors and a common framework for statistical inference on these measures. Illustrating these tools with Census and LFS microdata, the paper highlights the substantial decline in earnings shares and relative mean earnings levels of middleclass workers in Canada since 1980 and the corresponding dramatic rise in these measures for higher earners in the labour market.
Keywords: C12; C46; D31; D63; 330; Income inequality; inequality tool box; statistical inference